The effect of TCF bleaching before and after refining on the CMP pulp properties - Mohtaba Goli (Regional Information Center for Science and Technology (RICeST), 2016)
The objective of this study was determination of the best method of bleaching including refining and bleaching (RB) or bleaching and then refining (BR) on chemical mechanical pulp (CMP) for the production of newsprint. Wood raw material consists of mixed wood forest species was chipped and air dried to calculate the moisture content. Wood composition percentages for CMP pulping was 40% poplar, 30% maple, 7.5% oak, 7.5% alder, 7.5% willow, and 7.5% Persimmon. In order to remove heavy metal ions of pulp, the chelating was carried out with DTPA. TCF Bleaching carried out by 3% H2O2 and 2.5% NaOH based on dry weight of pulp with initial brightness of 44.6% ISO. Pulp bleaching was done in two stages, before and after the refining by laboratory PFI mill beater. Finally, handsheets were made from the RB and BR treated pulps and the sheet properties were evaluated according to TAPPI test methods. The results showed that BR treatment increased tensile, burst, tear indices, brightness, scattering coefficient, and density, but reduced yellowing, opacity, and light absorption coefficient. The results confirmed the conventional method of CMP pulp treatment (BR) in MWPI.